2022
DOI: 10.32493/jitk.v6i1.13199
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Jumlah Ekstraksi Bertingkat Terhadap Yield Antosianin pada Kulit Buah Naga Merah (Hylocereus polyrhizus)

Abstract: Dragon fruit skin has a very attractive red color that has the potential to produce anthocyanin pigments. Anthocyanin pigments are flavonoid compounds that are soluble in water and can be used as natural dyes in food and beverages. The purpose of this study was to see the effect of the number of multilevel extraction on the anthocyanin yield of dragon fruit peel extraction. 20 grams of dragon fruit peel powder with a mesh size of 20 was extracted in batches for 72 hours at room temperature using a mixture of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research and experiments into red dragon fruit peels utilization found red dragon fruit peels contain a large multitude of phytochemicals such as betacyanin, phenols, flavonoids, triterpenoids, steroids, tocopherols, vitamins, and carotenoid (Joshi and Prabhakar, 2020;Khuzaimah and Millati, 2022;Hendra et al, 2019;Kaul et al, 2020;Liana et al, 2019;Luu et al, 2021). These large *Corresponding author : Linda Chiuman Email : lindachiuman@unprimdn.ac.id multitudes of phytochemicals gave red dragon fruit peels great potential as a phytopharmaceutical agent.…”
Section: Introductionmentioning
confidence: 99%
“…Research and experiments into red dragon fruit peels utilization found red dragon fruit peels contain a large multitude of phytochemicals such as betacyanin, phenols, flavonoids, triterpenoids, steroids, tocopherols, vitamins, and carotenoid (Joshi and Prabhakar, 2020;Khuzaimah and Millati, 2022;Hendra et al, 2019;Kaul et al, 2020;Liana et al, 2019;Luu et al, 2021). These large *Corresponding author : Linda Chiuman Email : lindachiuman@unprimdn.ac.id multitudes of phytochemicals gave red dragon fruit peels great potential as a phytopharmaceutical agent.…”
Section: Introductionmentioning
confidence: 99%